Culture, industrial policy and international competitiveness of Colombian Pyme’s (SME’s) (2019)
So far the analysis related to the PyME production has focused on its components: organization, policies and technology. All these elements are considered as support for thePyMEs’ economic, productive and social management (Cardona, Cano, Ramírez, & Gutiérrez,2006). Thus, they help to determine the Colombian PyMEs’ relative competitiveness in the globalized environment. This article pursues the establishment of cultural variables that affect the production in the international business context through the analytic-synthetic method, in order to unravel the possible impact in terms of competitiveness as an industrial policy element.